Stimulasi Motorik Kasar Anak Usia 5-6 Tahun melalui Permainan Karet di Taman Kanak-kanak Thoyyibah Kota Sawahlunto - Susanti, Susanti; Ismet, Syahrul (Lembaga Yasin AlSys, 2025)
The development of gross motor skills is related to children's ability to move larger body parts, such as their hands and feet. Good gross motor skills in children also influence their self-confidence when interacting and socializing with their surroundings and peers. One effort to improve children's gross motor skills at Thoyyibah Kindergarten in Sawahlunto City is through rubber band games. This study is a Classroom Action Research (CAR) conducted on 10 children, consisting of 5 boys and 5 girls, in December 2024 and January 2025. The research refers to the model developed by Suharsimi Arikunto, which includes four main steps: planning, implementation, observation, and reflection. The study was conducted in two cycles, with Cycle I consisting of three meetings and Cycle II consisting of two meetings. Research data were collected through observation and documentation techniques. The data analysis technique used in this study is qualitative data analysis. The results of the study show an overall improvement in children's gross motor skills across all measured variables and indicators based on field observations.